Do reported intangible assets create a better information environment? - Nittikorn Suwansin; Napaporn Likitwongkajon; Pinprapa Sangchan (Global Business & Finance Review (GBFR), 2024)
Purpose: This study investigates whether the identifiable intangible assets (IIA), goodwill (GW), and research and development expense (R&D) reported in the financial statements and annual reports of firms on the Stock Exchange of Thailand (SET) can improve the information environment, as represented by a narrower bid-ask spread in the capital market. Additionally, this study explores the impact of intangible asset disclosure scores on the information environment. Design/methodology/approach: This study tests the association between reported intangible assets, intangible asset disclosure score, and bid-ask spread. The sample is 2,691 firm-year observations in SET from 2012-2021, and ordinary least squares (OLS) regression is used to test the hypothesis. Findings: The results found that IIA and R&D are associated with the information environment. It is reported that IIA and bid-ask spread have a positive relationship, whereas R&D and bid-ask spread have a negative relationship. In addition, the intangible asset disclosure score can also reduce bid-ask spread. Research limitations/implications: This study highlights the benefits of intangible assets, which can help bridge the information gap. However, the intangible asset disclosure score is determined through self-index construction. This process involves discretion and may be prone to errors. Furthermore, using the bid-ask spread as the sole indicator of the information environment might be inadequate. Originality/value: Research on information asymmetry about intangible assets in Thailand is scarce. This study provides empirical evidence to support the benefit of some intangible assets in reducing asymmetric information among investors. By utilizing the intangible asset disclosure score, including mandatory and voluntary disclosure, it is also possible to observe how different disclosure quality levels impact the information environment.
Keywords: 650; Intangible Assets; Information Environment; Bid-ask Spread